2002
DOI: 10.2322/tjsass.45.139
|View full text |Cite
|
Sign up to set email alerts
|

GHTA Spot-Welding Experiments of Aluminum and Titanium Plates under a Simulated Space Environment.

Abstract: GHTA (Gas Hollow Tungsten Arc) welding experiments were conducted under a simulated space environment that consists of vacuum and microgravity. A vacuum chamber for the experiments was placed in the aircraft cabin. Aluminum and titanium plates were employed as work pieces. The experiments prove that the arc discharge phenomena, the welding phenomena, and the microstructure of welded metal receive almost no effect from gravity. Moreover, it is also demonstrated that the weld metal of the plate welded under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…The magnitude of the gravity-or densitydriven buoyancy effect scales with the Rayleigh number (R a ), R a = β g ∆T D 3 ν -1 κ -1 (5) The magnitude of surface-tension-driven convection scales with the Marangoni number (M a ), M a = -∂σ/∂T ∆T D µ -1 κ -1 (6) In these equations, β = -1/ρ(∂ρ/∂T) is the thermal-expansion coeffi cient, ∂σ/∂T is the temperature-dependence of surface tension, g is the acceleration due to gravity, ∆T is the temperature gradient, D is a characteristic length, ν is the kinematic viscosity, µ is the dynamic viscosity, and κ is the thermal diffusivity. The relative magnitude of the Marangoni and gravity-driven buoyancy effects must be compared to determine which effect dominates the physical state of the melt pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the gravity-or densitydriven buoyancy effect scales with the Rayleigh number (R a ), R a = β g ∆T D 3 ν -1 κ -1 (5) The magnitude of surface-tension-driven convection scales with the Marangoni number (M a ), M a = -∂σ/∂T ∆T D µ -1 κ -1 (6) In these equations, β = -1/ρ(∂ρ/∂T) is the thermal-expansion coeffi cient, ∂σ/∂T is the temperature-dependence of surface tension, g is the acceleration due to gravity, ∆T is the temperature gradient, D is a characteristic length, ν is the kinematic viscosity, µ is the dynamic viscosity, and κ is the thermal diffusivity. The relative magnitude of the Marangoni and gravity-driven buoyancy effects must be compared to determine which effect dominates the physical state of the melt pool.…”
Section: Discussionmentioning
confidence: 99%
“…Masubuchi and Nayama 3 observed that in microgravity, the weld bead free surface did not contain ripples, which form in a terrestrial environment. Wang and Tandon 4 reported increases in weld depth and surface ripples in microgravity compared to in 1 g. Suita et al 5 concluded that microstructure development in the weld metal was unaffected by simulated changes in gravity.…”
Section: Introductionmentioning
confidence: 99%
“…が行われ, 微小重力環境が溶接現象に及ぼす影響が調査され ている.著者らは 1993 年に中空タングステン電極を使用す る宇宙 GHTA(Gas Hollow Tungsten Arc)溶接法 12,13) を提案 した.1998 年には真空チャンバを搭載した航空機の放物飛 行で得られる模擬宇宙環境下での GHTA 溶接実験 14,15)…”
unclassified
“…We are now performing research and development of the GHTA welding process [6][7][8][9][10] for space applications. The high-frequency device employed to start the arc in previous conventional experiments may be an obstacle for electric devices placed on the ISS due to the creation of electromagnetic noise.…”
Section: Introductionmentioning
confidence: 99%